Foreword - Zs. Varga, András (Federalism as the Future of the Diverse EU?, 2025)
The research explores the constantly evolving federal nature of the European Union in the post-Lisbon Treaty era, where Member States coexist within a complex institutional, legal and economic framework. The research posits the hypothesis that the European Union is currently in a transitional phase between the principles of intergovernmentalism and federalism. This transitional entity is characterised by a dynamic interplay between national sovereignty and the processes of supranational integration, in the context of the challenges posed by globalisation. The book investigates the question of whether the EU should move towards a more federalist model or maintain a cooperative coexistence model, in which powers remain primarily with the Member States. It also focuses on the differing roles and ambitions of EU institutions as opposed to those of individual Member States. The research draws on regional experiences to advocate for the examination of alternative governance models that emphasise cooperation over centralisation.